2009
DOI: 10.1093/geronb/gbp095
|View full text |Cite
|
Sign up to set email alerts
|

Delineating Terminal Change in Subjective Well-Being and Subjective Health: Brief Report

Abstract: The present study investigated whether several evaluative indicators of subjective well-being (SWB) and subjective health decline as death approaches and which of them shows a stronger decline. Using three-wave longitudinal data from deceased participants of the Cross-Sectional and Longitudinal Aging Study (N = 1,360; age range 75-94 at T1= Time 1), we found a stronger decline in most evaluative indicators when plotted by distance-to-death relative to distance from birth. After controlling for background chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 16 publications
8
65
1
Order By: Relevance
“…The amount of variance accounted for was higher in the mortality-related model of self-esteem change at the end of life (.16; AIC = 17774) compared to the age-related model (.09; AIC = 17804). Such results concur with previous reports that time-to-death provides for a more efficient description of between-person differences in late-life change (Palgi, et al, 2010). In follow-up analyses, we also included both age and mortality into one combined growth-curve model.…”
Section: Self-esteem Late In Life: Age-and Mortality-related Change Tsupporting
confidence: 87%
See 1 more Smart Citation
“…The amount of variance accounted for was higher in the mortality-related model of self-esteem change at the end of life (.16; AIC = 17774) compared to the age-related model (.09; AIC = 17804). Such results concur with previous reports that time-to-death provides for a more efficient description of between-person differences in late-life change (Palgi, et al, 2010). In follow-up analyses, we also included both age and mortality into one combined growth-curve model.…”
Section: Self-esteem Late In Life: Age-and Mortality-related Change Tsupporting
confidence: 87%
“…Evidence for precipitous proximate-to-death declines that are often considerably steeper than the typical age-related effects has primarily accumulated in cognitive ability domains (for overviews, see Bäckman & MacDonald, 2006;Berg, 1996;Small & Bäckman, 1999). However, there is an increasing body of research showing that many aspects of well-being also show steep end-of-life declines (Berg et al, 2011;Diehr et al, 2002;Mroczek & Spiro, 2005;Palgi et al, 2010). There is even initial evidence to suggest that terminal decline is a highly pervasive phenomenon that affects many different domains, including those often considered relatively stable across old and very old age (Gerstorf, Ram, et al, 2012).…”
Section: Self-esteem Trajectories At the End Of Lifementioning
confidence: 99%
“…Moreover, these studies also introduced a new perspective by analysing life satisfaction not merely as a function of chronological age (= distance from birth), but also as a function of 'distance from death', which is a variable presumably related to mortality processes. Distance from death explained more variance of change in life satisfaction than did chronological age (see also Palgi et al, 2010). Analyses with distance from death as independent variable also revealed two different stages of change in life satisfaction: A phase of slight decline occurring in a larger temporal distance from death ('preterminal decline') and a phase of a much steeper decline (thus, at least by factor 2) about four years before death ('terminal decline').…”
Section: Mainmentioning
confidence: 88%
“…In an attempt of identifying possible mechanisms in action for time-to-death-related changes in life satisfaction, Gerstorf et al found initial level of comorbidity to predict level of life satisfaction, but not change in life satisfaction related to death (Gerstorf et al 2008). In a recent study, Palgi et al confirmed these results in their study of terminal change in subjective well-being; the inclusion of gender, marital status, place of residence, cognitive function and diagnoses did not reduce the terminal change effects (Palgi et al 2010). Two limitations characterize these studies.…”
mentioning
confidence: 90%